Development of an Index of Socio-Emotional Competence for Preschool Children in the Growing Up in New Zealand Study - Ahmad, Sahrish; Peterson, Elizabeth R.; Waldie, Karen E.; Morton, Susan M. B. (Frontiers in Education, 2019)
Growing international recognition of the importance of socio-emotional competence has led to calls to understand the prevalence and development of such competence in young children. However, socio-emotional competence is a multifaceted concept and hence difficult to track. The present research describes the processes we used to develop an index of socio-emotional competence in preschool children taking part in the Growing Up in New Zealand (GUiNZ) study. We draw on data collected from 6156 children when they were 9 months, 2 years and 4.5 years of age. Twenty-six variables from seven measures were found to provide conceptual coverage of socio-emotional competence and had adequate discriminatory power and internal consistency. Our final sample consisted of 4839 participants who had adequate data on the variables of interest. Exploratory factor analysis led to the emergence of three dimensions: easy-going, regulation and exuberance. Multiple methods of weighting (equal, empirical and time-based) were used to calculate the index, which resulted in eight possible index versions. The index with equally weighted variables (including observations scores) and dimension scores, and time weighted scores of socio-emotional competence at each data collection wave, was found to be the most empirically sound. Both categorical and continuous index scores were calculated to allow for variety of later analytical usage. Our findings may be of interest to policy-makers and clinicians who could use this knowledge to better understand the trajectories of development of socio-emotional competence, and factors associated with any derived patterns and change. This may also help identify children at risk of poor socio-emotional development as early as possible, which may be of interest to those looking to mitigate the risk of poor socio-emotional development.